(a+b)^3+(a-b)^3 это числитель делить на 2ab(a^2+3b^2) и минус просто 1 нужно это выражение

brandenberg brandenberg    3   12.03.2019 02:40    3

Ответы
botvinaanna80 botvinaanna80  24.05.2020 23:19

(a+b)^3+(a-b)^3 / (2ab(a^2+3b^2)) - 1 =

=( a^3+3a^2b+3ab^2+b^3  +   a^3-3a^2b+3ab^2-b^3) /(2ab(a^2+3b^2)) - 1 =

=(2a^3+6ab^2) /(2ab(a^2+3b^2)) -(2ab(a^2+3b^2)) /(2ab(a^2+3b^2)) =

=(2a(a^2+3b^2) -2ab(a^2+3b^2)) /(2ab(a^2+3b^2)) =

=(2a-2ab)(a^2+3b^2)  /(2ab(a^2+3b^2)) = (2a-2ab) /(2ab)=2a(1-b)/(2ab)=

= (1-b) / b

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра